2001
DOI: 10.1002/1615-9861(200107)1:7<871::aid-prot871>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of glass wool as an attachment surface for studying phenotypic changes inPseudomonas aeruginosa biofilms by two-dimensional gel electrophoresis

Abstract: Two-dimensional polyacrylamide gel electrophoresis was used to demonstrate phenotypic differences between Pseudomonas aeruginosa biofilm cells and the planktonic counterpart cells under defined culture conditions. Glass wool was used as a substratum for cell attachment as it affords a large surface-to-volume ratio (1 g with a mean diameter of 15 microns = 1300 cm2), supports the growth of biofilms, allows for free movement of cells between the inter-strand spaces, and it facilitates the exchange of nutrients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…An increase in the PGW population would be ascribed either to growth or detachment of cells from the biofilm, while a proportional increase in the attached population implies a net biofilm gain, due either to growth or recruitment from the suspended population. This restricted propensity to form biofilm is similar to the distribution observed for Pseudomonas aeruginosa , but much lower than reported previously for B. cereus DL5 isolated from a dairy cleaning solution . The average biofilm density corresponded to 3 × 10 6 CFU/cm 2 (Figure ).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…An increase in the PGW population would be ascribed either to growth or detachment of cells from the biofilm, while a proportional increase in the attached population implies a net biofilm gain, due either to growth or recruitment from the suspended population. This restricted propensity to form biofilm is similar to the distribution observed for Pseudomonas aeruginosa , but much lower than reported previously for B. cereus DL5 isolated from a dairy cleaning solution . The average biofilm density corresponded to 3 × 10 6 CFU/cm 2 (Figure ).…”
Section: Resultssupporting
confidence: 77%
“…The third component discriminated between the PGW proteome and all others (Figure C) . B. cereus DL5 and P. aeruginosa studied under similar conditions also displayed a PGW proteome distinct from its planktonic and biofilm counterparts by expressing some unique protein spots. , Component 3 of this PCA offered evidence that the PGW phenotype was not the result of a mixture of released biofilm and stationary phase planktonic cells. Rather, these planktonic cells constituted a unique phenotype, expressed as response to either the proximal biofilm or periodic contact with the glass surface.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Earlier studies have shown that as many as 30-40% of the proteins present in bacterial cell walls differ between sessile and planktonic bacteria (Coghlan, 1996). Furthermore, BF of P. aeruginosa developed on glass wool revealed changes in protein profile (Steym et al, 2001). Studies on starved cells of A. hydrophila have shown that about five outer membrane proteins were lost with the expression of three new proteins compared to FC (Rahman et al, 1998).…”
Section: Protein Profile Of Biofilm and Free Cells Of V Anguillarummentioning
confidence: 99%